2009
DOI: 10.1098/rsbl.2009.0100
|View full text |Cite
|
Sign up to set email alerts
|

Sex allocation and sexual conflict in simultaneously hermaphroditic animals

Abstract: Links between sex allocation (SA) and sexual conflict in simultaneous hermaphrodites have been evident since Charnov's landmark paper published 30 years ago. We discuss two links, namely the potential for sexual conflict over SA between sperm donor and recipient, and the importance of post-copulatory sexual selection and the resulting sexual conflict for the evolution of SA. We cover the little empirical and theoretical work exploring these links, and present an experimental test of one theoretical prediction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 21 publications
(32 reference statements)
5
65
0
Order By: Relevance
“…Individuals of this species are capable of adjusting their sex allocation (i.e., the reproductive investment into the male versus the female sex function) in response to the social group size (i.e., the number of potential mates) that they experience. Such an adjustment is in agreement with a central prediction of sex allocation theory for simultaneous hermaphrodites (for a review, see Schärer 2009), and several studies have demonstrated for M. lignano that individuals that were raised in larger groups have bigger testes (e.g., Schärer and Ladurner 2003;Schärer et al 2005;Schärer and Vizoso 2007;Schärer and Janicke 2009).…”
Section: Communicated By T Mooresupporting
confidence: 56%
“…Individuals of this species are capable of adjusting their sex allocation (i.e., the reproductive investment into the male versus the female sex function) in response to the social group size (i.e., the number of potential mates) that they experience. Such an adjustment is in agreement with a central prediction of sex allocation theory for simultaneous hermaphrodites (for a review, see Schärer 2009), and several studies have demonstrated for M. lignano that individuals that were raised in larger groups have bigger testes (e.g., Schärer and Ladurner 2003;Schärer et al 2005;Schärer and Vizoso 2007;Schärer and Janicke 2009).…”
Section: Communicated By T Mooresupporting
confidence: 56%
“…Until recently, most models of sperm competition have treated the sperm recipients as a passive vessel in which sperm from different sperm donors compete for access to ova. However, as Charnov [18] pointed out in his seminal 1979 paper, reciprocal mating may lead to post-copulatory female choice (later termed cryptic female choice [74,75]; see also [76]). Cryptic female choice is expected to be prevalent in hermaphrodites because reciprocal mating strategies lead to the receipt of sperm from individuals that are unattractive as fathers.…”
Section: (C) Cryptic Female Choicementioning
confidence: 99%
“…Hence, there will be much to gain from the consideration of kin structure across all studies of sexual conflict. Schärer & Janicke (2009) also do much to highlight the fact that the links between sex allocation and sexual conflict deserve further study across hermaphrodites and organisms with separate sexes. Similarly, Bedhomme et al (2009) initiate a discussion of the differences in how traits selected under the influence of sexual conflict will behave in hermaphrodites in comparison to plants and animals with separate sexes.…”
Section: (D) Sexual Conflict Coevolution Evolutionary Chases and Rementioning
confidence: 99%
“…Differences in variance between sex functions are also therefore important in species without separate sexes. Schärer & Janicke (2009) nicely extend this approach by examining conflicts over sex allocation between sperm donors and sperm recipients in hermaphrodites, and the importance of post-copulatory sexual selection. Sperm-trading and the influence of conflicts of interest between different hermaphrodite partners are themes that were also tackled by Charnov (1979).…”
Section: (D) Sexual Conflict Coevolution Evolutionary Chases and Rementioning
confidence: 99%